Methods for policy research : taking socially responsible action - Majchrzak, Ann; Markus, M. Lynne (Applied social research methods series, 2014)
Looking at the analysis of policies with a view to changing them, this book is written by an expert on policy research and shows ways of presenting alternatives to policy-makers